Sputtering and characterization of ZnO thin film for hard disk smart slider - Zhang, Hang (2012)
In order to maximize the high storage capacity for hard disc, we need to adjust the flying height at lower position, because low position flying height can sense larger area of disc. When the recording density reaches 1Tb/in2 or more, the flying height will be only 1-2nm or less. This paper demonstrates the substrate dependency of zinc oxide growth in radio-frequency sputtering method. Different deposition conditions were carried out to find out the best operating parameters to grow a good quality ZnO thin film. ZnO thin films were deposited on Si and SiO2 substrate with Au layer using RF Magnetron sputtering system. The effect of RF powers, working pressure and O2/ (O2+Ar) gas ratios were studied and analyzed. The properties of the ZnO thin film was then characterized by using X-ray Diffractometer (XRD) and Field Emission Scanning Electron Microscopy (FESEM)/ Energy Dispersive X-ray (EDX).